Micropollutant removal and nutrient recovery for sustainable management of urban wastewater - Zhang, Jiefeng (2015)
The continuous discharge of nutrients and micropollutants such as pharmaceutically active compounds (PhACs) potentially create a threat to urban aquatic environment and water safety. This issue is extremely important for some metropolitans that rely on the renewable/reclaimable water resources such as Singapore. This study explores new approaches to improve the current wastewater management practice particularly in terms of nutrient recovery and micropollutant mitigation from both scientific and engineering perspectives.